Pengaruh Variasi Suhu dan Waktu Terhadap Pembuatan Kertas Karton dari Pelepah Kelapa Sawit Menggunakan Metode Kraft - Grace Stevi Wildiana Manik; Muhammad Syukri (Lembaga Penelitian dan Pendidikan (LPP) Kalibra, 2026)
As the oil palm plantation industry continues to expand in Indonesia, the amount of waste generated also increases, including solid waste in the form of oil palm fronds. This waste has not been utilized optimally, even though its availability increases with the age of the plantation. One potential utilization of oil palm fronds is as a raw material for paperboard production because they contain 51.58% cellulose. This study aimed to determine the effect of cooking temperature and cooking time on the production of paperboard made from oil palm fronds. The research was conducted at the Chemical Industrial Process Laboratory, University of Sumatera Utara, from March to April 2026. The study consisted of two factors. The first factor was cooking temperature with three levels: L1 (90°C), L2 (95°C), and L3 (100°C). The second factor was cooking time with three levels: T1 (90 minutes), T2 (120 minutes), and T3 (150 minutes). The results showed that cooking temperature and cooking time had a highly significant effect on two observed parameters, namely tensile strength (18.05 kN/m) and water absorption (80.00 g/m²), but did not have a significant effect on grammage (g/m²).